Ornithological Observations in Northeast Greenland between 76°00´ and 78°00´ N.Lat. 1969-71. - Meltofte, Hans (Meddelelser om Grønland, 1975)
The present paper is a report of observations made during a two-year stay at the weather station at Danmarks Havn 1969-71. An avifaunistic status of the area is given, and the results are compared with the few earlier reports. Several changes are demonstrated, and relations to climatic conditions are discussed. Special information is given on the colonies of Branta leucopsis and on two moulting areas of Anser fabalis brachyrhynchus, two species in which significant changes can be traced. 1970 was an especially unfavourable ’late’ year, and the breeding cycle of some species was considerably delayed. Further, the results of a simple population-census, especially of breeding waders are given.